Gasprinsky`s new teaching method - Ismail Kerimov (Крымское историческое обозрение)
The article discusses the issue of the new methodology “Usul-i- jedit” (“New methods of teaching reading and writing”), developed by I. Gasprinsky at the very beginning of 1880 in the Crimean Tatar primary schools. It traces the spread of “Usul-i-jedit” in Muslim schools of Volga region, Caucasus, Central Asia, Turkey, Iran, India and other regions. It shows how the reforms of the educational system of that time influenced to dynamics and quality of the education. Based on little-known sources, Gasprinsky`s personal contribution to the development of the educational process in Muslim countries is reflected.